Helicobacter pylori infection treatment in the United States: clinical consequences and costs of eradication treatment failure. (3rd April 2022) - Shah, Shailja; Hubscher, Elizabeth; Pelletier, Corey; Jacob, Rinu; Vinals, Lydia; Yadlapati, Rena
ABSTRACT: Introduction: Helicobacter pylori (Hp) is causal in benign and malignant gastrointestinal diseases. Accordingly, current guidelines recommend Hp eradication in patients with active infection. Unfortunately, treatment failure is common, exposing patients to complications associated with persistent Hp infection and consequences of repeated treatment, including promotion of antibiotic resistance. In the United States (US), data regarding eradication rates with available therapies are limited. Moreover, the clinical and economic burden of eradication treatment failure have not been thoroughly described. Areas covered: We aimed to characterize Hp eradication rates and the clinical consequences and associated costs of persistent Hp infection among US adults. We conducted focused literature reviews using initial searches in Embase, MEDLINE, and Cochrane Database of Systematic Reviews via Ovid followed by manual searches to identify relevant publications. Expert opinion: Hp eradication rates were suboptimal, with most studies reporting rates ≤80% with clarithromycin-based triple therapy and bismuth quadruple therapy. There was direct evidence supporting numerous benefits of successful Hp eradication, including decreased risk of recurrent or complicated peptic disease and non-cardia gastric cancer. Cost benefits of eradication were related to mitigation of conditions associated with persistent Hp infection, (e.g. complicated peptic ulcer disease, and gastric cancer) which altogether exceed US5.3 billion.